Relationship between head posture and the severity of obstructive sleep apnea. - Sökücü, Oral; Okşayan, Rıdvan; Uyar, Meral; Ademci, Kadriye Ebru; Üşümez, Serdar (My University, 2016)
The objective of this study was to compare the head posture of patients with obstructive sleep apnea (OSA) having different levels of severity with that of control subjects.

One hundred subjects participated in this study. Seventy-five subjects underwent overnight polysomnography in a sleep laboratory and were allocated into "mild," "moderate," or "severe" OSA groups, and 25 subjects with no complaints regarding OSA were allocated into 1 group and served as the controls. Cephalometric radiographs were obtained from all participants in natural head position. Craniocervical, craniovertical, and cervicovertical angles were measured in the groups. Data were analyzed using the least significant difference.

The results showed significant differences between the OSA groups and the control group, and among the test groups, in all craniocervical, craniovertical, and cervicovertical angles (P <0.05), except for 1 craniovertical measurement (P >0.05). There were no significant differences in this measurement among the test groups and in any measurement between the mild and moderate OSA groups (P >0.05).

Head posture showed significant differences in patients with OSA. In general, the more severe the OSA, the more extended the natural head position as indicated by increases in the craniocervical angles. The cervical posture parameters may indicate existing OSA.